Impact of influenza on hospitalization rates in children with a range of chronic lung diseases. Issue 3 (30th January 2019) - Homaira, Nusrat; Briggs, Nancy; Oei, Ju‐Lee; Hilder, Lisa; Bajuk, Barbara; Snelling, Tom; Chambers, Georgina M.; Jaffe, Adam
Abstract : Background: Data on burden of severe influenza in children with a range of chronic lung diseases (CLDs) remain limited. Method: We performed a cohort study to estimate burden of influenza‐associated hospitalization in children with CLDs using population‐based linked data. The cohort comprised all children in New South Wales, Australia, born between 2001 and 2010 and was divided into five groups, children with: (a) severe asthma; (b) bronchopulmonary dysplasia (BPD); (c) cystic fibrosis (CF); (d) other congenital/chronic lung conditions; and (e) children without CLDs. Incidence rates and rate ratios for influenza‐associated hospitalization were calculated for 2001‐2011. Average cost/episode of hospitalization was estimated using public hospital cost weights. Results: Our cohort comprised 888 157 children; 11 058 (1.2%) had one of the CLDs. The adjusted incidence/1000 child‐years of influenza‐associated hospitalization in children with CLDs was 3.9 (95% CI: 2.6‐5.2) and 0.7 (95% CI: 0.5‐0.9) for children without. The rate ratio was 5.4 in children with CLDs compared to children without. The adjusted incidence/1000 child‐years (95% CI) in children with severe asthma was 1.1 (0.6‐1.6), with BPD was 6.0 (3.7‐8.3), with CF was 7.4 (2.6‐12.1), and with other congenital/chronic lung conditions was 6.9 (4.9‐8.9). The cost/episode (95% CI) of influenza‐associated hospitalization was AUD 19 704 (95% CI: 11 715‐27 693) for children with CLDs compared to 4557 (95% CI: 4129‐4984) for children without. Discussion: This large population‐based study suggests a significant healthcare burden associated with influenza in children with a range of CLDs.